2018
DOI: 10.17532/jhsci.2018.543
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in primary healthcare professionals

Abstract: Introduction: The aim of this study was to assess the level of burnout syndrome among primary healthcare professionals in Canton Sarajevo and whether there is a link between the levels of burnout syndrome and sociodemographic parameters. Methods: We included a total of 300 primary healthcare professionals. The burnout syndrome level was measured by Maslach Burnout Inventory, consisting of 22 particles (3 subscales) measuring the level of emotional exhaustion (EE), depersonalization (DP), and personal acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Likewise, an unfavorable result on either one dimension of burnout was displayed by 22.9% of doctors and 18.3% of nurses. Regarding levels of all three dimensions of burnout, the results of this study are in line with a recent one using the same methodology,conducted in Sarajevo Canton (Džubur et al, 2018).However, compared to other burnout studies depersonalization is significantly lower, while personal accomplishment is higher (Pranjić, 2006;Selmanović et al, 2011;Stanković et al, 2019).Taken together, our results indicate that emotional exhaustion seems to be the most prominent dimension of burnout in our sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, an unfavorable result on either one dimension of burnout was displayed by 22.9% of doctors and 18.3% of nurses. Regarding levels of all three dimensions of burnout, the results of this study are in line with a recent one using the same methodology,conducted in Sarajevo Canton (Džubur et al, 2018).However, compared to other burnout studies depersonalization is significantly lower, while personal accomplishment is higher (Pranjić, 2006;Selmanović et al, 2011;Stanković et al, 2019).Taken together, our results indicate that emotional exhaustion seems to be the most prominent dimension of burnout in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…Scarcity of studies that employed MBI measurement of burnout in Bosnia and Herzegovina calls for more exploration of the topic showing a significant level of burnout, although rough comparison with other countries seems favorable (Pranjić, 2006;Toševski et al, 2006;Džubur et al, 2018). However, two studies conducted in single large health centers in Bosnia and Herzegovina showed somewhat worse picture (Selmanović et al, 2011;Stanković et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study was based on the MBI, and 20.9% of respondents had a high level of emotional exhaustion, 43.2% had a high level of depersonalization ( 36 ), and emotional exhaustion and depersonalization were suggested to be the foundation of burnout ( 5 ). Another survey based on MBI, conducted among primary health care providers in the Sarajevo Canton, showed that 25.3% of HCWs experienced a high level of emotional exhaustion and 17.7% experienced depersonalization ( 37 ). Research conducted among physicians in Croatia on a national level before the pandemic showed that 63% of all physicians experienced burnout, and 16% of physicians experienced all three forms of burnout ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of independent studies, based on different models of occupational stress (28)(29)(30)(31), have the same conclusions, and generally, one of the most serious consequences on the health-care professional's workability leaves burnout syndrome as a psychological state resulting from prolonged exposure to high-intensity stress during a professional engagement. The results of this study are consistent with the above and indicate that working conditions in the relation of stress and empathic capacity of health-care professionals are good predictors of workability.…”
Section: Discussionmentioning
confidence: 76%